Necrotizing Ulcerative Gingivitis, a Rare Manifestation as a Sequel of Drug-Induced Gingival Overgrowth: A Case Report - Marah Damdoum; Sudhir Rama Varma; Mohamed A. Jaber; Manjusha Nambiar (Case Reports in Dentistry)
Purpose. The purpose of this case report is to present a rare case of amlodipine-induced gingival overgrowth with a secondary formation of necrotizing ulcerative gingivitis involving the upper and lower arches of a 68-year-old female patient with a chief complaint of “swollen gums and pain on mastication which has been recurring for the past 5 years.” Materials and Methods. The treatment plan of this case was divided according to quadrants of the mouth. Each week, one quadrant was surgically excised, and the remaining quadrants were observed for any changes. The gingival overgrowths were excised using a 15 blade, and debris/plaque was removed with Gracey curettes. Results. Although full-mouth exodontia was performed, the patient unfortunately suffered with recurrences in GO. These results are suggestive of idiopathic causes of GO. Conclusion. Careful examination, physician referrals, and biopsy to rule out any specific anomalies and to assist in proper diagnosis are followed by sequential management of the case results in productive outcomes.